Epidemiology and risk factors of oral frailty among older people: an observational study from China - Yueheng Yin; Yue Zhao; Yang Fei; Ying Liu; Yun Ji; Enfang Shan; Shuzhen Niu; Ying Xing; Jingjing Ding; XianWen Li (BMC, 2024)
Abstract Objectives This study aimed to compare the prevalence of oral frailty among community-dwelling older people in Nanjing, China with the usage of different measurements, and to investigate the potential risk factors of oral frailty. Design Cross-sectional study. Setting and participants A total of 338 community-dwelling older people in Nanjing, China were recruited. Methods Oral frailty was measured based on the Oral Frailty Index-8 (OFI-8) scale and other measurement methods including the number of natural teeth (TN), repetitive saliva-swallowing test (RSST), and oral diadochokinesis (ODK). The chi-square test and the binary logistic regression analysis were performed to identify potential risk factors for oral frailty. Results There were 310 participants included in the analysis. Prevalence of oral frailty by using the OFI-8, OFI-8 + TN, OFI-8 + ODK, OFI-8 + TN + ODK and RSST measurement methods were 69.0%, 27.4%, 51.9%, 21.0% and 2.9%, respectively. Passive smoking (OR = 2.04; 95%CI 1.03-4.03), being widowed/unmarried (OR1 = 2.53; 95%CI 1.25-5.10; OR2 = 2.94; 95%CI 1.12-7.77), pre-frailty (OR = 1.76; 95%CI 1.03-3.01), frailty (OR = 3.01; 95%CI 1.39-6.54), and aged 80 years and above (OR = 3.99; 95%CI 1.35-11.81) were found to be risk factors of oral frailty by the usage of the four kinds of measurement methods. Conclusions and implications The definition and diagnostic criteria of oral frailty are strongly needed to be unified in future research. Only subjective assessment is not enough for assessing oral frailty. Among objective indicators, RSST is not suitable as a screening method for oral frailty. In addition, objective indicators including TN and ODK should be valued for early screening and preventive interventions. The risk factors of oral frailty include physical frailty, passive smoking, and being widowed.